Coaching in leadership development - Korotov, Konstantin (Henry Stewart Talks, 2015)
General & specific definitions of coaching, The coaching for leadership development process, Coaching vs. other methods, Special cases in leadership development coaching, Topics that come up in coaching sessions, Evaluation of the effectiveness of coaching, The qualification challenge and its solution, How coaches develop themselves, After the coaching, Coaching and therapy confusion